Kikuchi's Disease: A Rare Cause of Fever and Lymphadenopathy - A Vivekanandarajah; B Krishnarasa; M Hurford; S Gupta (SAGE Publishing, 2012)
Kikuchi's disease is a benign condition that occurs in women. A young woman presented to the hospital with fevers and cervical lymphadenopathy. Infectious work-up was negative except for streptococcus pharyngitis. Imaging studies revealed the presence of diffuse cervical and axillary lymphadenopathy. The fevers persisted and she underwent excisional cervical lymph node biopsy that revealed histiocytic necrotizing lymphadenitis corresponding to a benign diagnosis of Kikuchi's disease. Three months later, the patient was afebrile and there was complete resolution of the cervical lymphadenopathy.